Lactobacillus from fermented bamboo shoots prevents inflammation in DSS-induced colitis mice via modulating gut microbiome and serum metabolites - Xiangru Liu; Xiaoling Lu; Hao Nie; Jing Yan; Zhiwen Ma; Hailin Li; Shixin Tang; Qi Yin; Jingfu Qiu (Food Science and Human Wellness)
Fermented bamboo shoots (FBS) is a region-specific food widely consumed in Southwestern China, with Lactobacillus as the predominant fermenting bacteria. However, the probiotic potential of Lactobacillus derived from FBS reminds largely unexplored, especially for diseases with a low prevalence in areas consuming FBS, namely, inflammatory bowel disease. In this study, Lactiplantibacillus pentosus YQ001 and Lentilactobacillus senioris YQ005 were screening by in vitro probiotic tests to further investigate the probioticlike bioactivity in dextran sulfate sodium (DSS)-induced ulcerative colitis (UC) mouse. They exhibited more positive probiotic effects than Lactobacillus rhamnosus GG in preventing intestinal inflammatory response. The results revealed that both strains improved the abundance of deficient intestinal microbiota in UC mice, including Muribaculaceae and Akkermansia. In the serum metabolome, they modulated the DSS-disturbed levels of metabolites, with significant increment of cinnamic acid. Meanwhile, they reduced the expression levels of interleukin-1β (IL-1β), interleukin-6 (IL-6) inflammatory factors and increased zonula occludens-1 (ZO-1), Occludin, and cathelicidin-related antimicrobial peptide (CRAMP) in the colon. Consequently, these results demonstrated that Lactobacillus spp. isolates derived from FBS showed promising probiotic activity based on the gut microbiome homeostasis modulation, anti-inflammation and intestinal barrier protection in UC mice.